Stratospheric influence on ECMWF sub‐seasonal forecast skill for energy‐industry‐relevant surface weather in European countries - Büeler, Dominik; Beerli, Remo; Wernli, Heini; id_orcid:0 000-0001-9674-4837; Grams, Christian M. (Wiley, 2020)
Meteorologists in the energy industry increasingly draw upon the potential for enhanced sub‐seasonal predictability of European surface weather following anomalous states of the winter stratospheric polar vortex (SPV). How the link between the SPV and the large‐scale tropospheric flow translates into forecast skill for surface weather in individual countries – a spatial scale that is particularly relevant for the energy industry – remains an open question. Here we quantify the effect of anomalously strong and weak SPV states at forecast initial time on the probabilistic extended‐range reforecast skill of the European Centre for Medium‐Range Weather Forecasts (ECMWF) in predicting country‐ and month‐ahead‐averaged anomalies of 2 m temperature, 10 m wind speed, and precipitation. After anomalous SPV states, specific surface weather anomalies emerge, which resemble the opposing phases of the North Atlantic Oscillation. We find that forecast skill is, to first order, only enhanced for countries that are entirely affected by these anomalies. However, the model has a flow‐dependent bias for 2 m temperature (T2M): it predicts the warm conditions in Western, Central and Southern Europe following strong SPV states well, but is overconfident with respect to the warm anomaly in Scandinavia. Vice versa, it predicts the cold anomaly in Scandinavia following weak SPV states well, but struggles to capture the strongly varying extent of the cold air masses into Central and Southern Europe. This tends to reduce skill (in some cases significantly) for Scandinavian countries following strong SPV states, and most pronounced, for many Central, Southern European, and Balkan countries following weak SPV states. As most of the weak SPV states are associated with sudden stratospheric warmings (SSWs), our study thus advices particular caution when interpreting sub‐seasonal regional T2M forecasts following SSWs. In contrast, it suggests that the model benefits from enhanced predictability for a considerable part of Europe following strong ...